Erdi Aroa eta Nafarroako erresuma : Historia 3. zikloan / [egilea, Mixel Ernaga ... et al.] - Ernaga, Mixel; Bidegain, Maialen; Erdozainzi, Maite; Hiribarren, Maialen (: Ikas, 2005)
Historia saileko lehen atala.